An investigation of the metabolic, hormonal and anthropometric characteristics of the menopausal transition in black urban South African women - Jaff, Nicole Gusti (My University, 2016)
Background and Objectives: The Study of Women Entering and in Endocrine Transition (SWEET) was developed to examine differences in metabolic, hormonal, and anthropometric parameters in black urban South African women at different stages of the menopause transition (MT). Little data are available on accurate staging of the menopausal transition for sub-Saharan African women. There is a plethora of data on this and related subjects in Western women, but little available research on changes in body composition or risk of metabolic syndrome (MetS) in the MT in midlife black South African women, although obesity is prevalent in this group, and there is a high instance of both diabetes and hypertension. The prevalence of HIV infection is also high in these women but it is not known whether this may affect the symptoms and conditions of the MT, contribute to changes in body composition or increased risk of MetS and cardiovascular disease (CVD). No prior study in sub-Saharan Africa has used the Stages of Reproductive Aging Workshop + 10 (STRAW + 10) criteria to stage reproductive aging or assessed their reliability in classifying ovarian status. The MT is closely associated with changes in body composition including lower bone mineral density, decreased lean muscle mass, increased body mass index (BMI) and adiposity, particularly increased central adiposity. Abdominal obesity is a key risk factor for MetS. This, and the subsequent risk of CVD appear to increase as women transition into menopause. It is unclear if this is due to reproductive or chronological aging, or both combined. Aims: (1) To assess the usefulness of the STRAW + 10 criteria in staging ovarian aging in black South African women. (2) To determine whether there are differences in body adiposity, lean muscle mass, and bone mineral density (BMD) across reproductive groups and ascertain the main correlates of these variables. (3) To determine in this population, if the risk of MetS and the levels of its components and related metabolic factors, differ between women at different stages of the MT and to explore the possible determinants. (4) To investigate whether the high prevalence of HIV infection in these women affects the age at menopause, menopausal symptoms, body composition, and metabolic variables in midlife black South African women. Methods: Participants in this cross-sectional study were 702 black urban African women aged 40 to 60 years. The stages of reproductive aging were categorized using STRAW + 10 criteria. The Menopause Rating Scale was used to measure the prevalence of menopausal symptoms including vasomotor symptoms. Study-specific questionnaires were used to obtain relevant demographic and lifestyle data. Blood levels of follicle stimulating hormone (FSH), estradiol (E2), dehydroepiandrosterone (DHEA), dehydroepiandrosterone sulfate (DHEAS), testosterone (T) and sex hormone blinding globulin (SHBG), insulin, lipids, glucose, leptin and adiponectin were measured. Simple measures of body anthropometry (weight, height, waist and hip circumference) were obtained. Body composition was measured using dual-energy X-ray absorptiometry (DXA) and ultrasonography. Human immunodeficiency virus (HIV) status was assessed using a point-of-care method. Metabolic syndrome and diabetes were diagnosed using internationally recognized criteria. Results: Reported age at final menstrual period (FMP) was higher in subjects interviewed within 4 years of FMP (49.0±3.80) than in subjects interviewed ≥10 years after FMP (42.0±4.06; p<0.0005). Human immunodeficiency virus (HIV) status had no effect on menopause symptoms. A BMI ≥35 kg/m2 was associated with severe vasomotor symptoms. Estradiol (p<0.0005), SHBG (p<0.0005) and DHEAS (p=0007) were significantly lower in post- than premenopausal groups, whilst FSH was higher (p<0.0005). Whole body lean mass (p=0.002) and BMD (p<0.0005) were significantly lower in postmenopausal compared to premenopausal groups. Multivariable linear regression models and ANCOVA demonstrated that the lower lean mass was related to the high postmenopausal FSH levels, whilst the lower BMD was partially explained by the low postmenopausal E2 levels. Use of antiretroviral therapy (ART) correlated negatively with total fat mass (β=-2.92, p=0.008) and total bone mineral content (BMC; β=-78.8, p=0.003). The MetS was highly prevalent (49.6%). Levels of total cholesterol (p<0.0005), LDL (p<0.0005), triglyceride (p=0.01), systolic (p<0.0005) and diastolic (p<0.05) blood pressure were all significantly higher in postmenopausal compared to pre-menopausal groups whilst there was a trend for glucose levels (p=0.05) and MetS prevalence (p=0.05) to also be higher. Multiple regression analyses and ANCOVA showed that the higher levels of cholesterol and LDL were related to higher FSH concentrations whilst elevation in systolic blood pressure was linked to lower estradiol levels. The higher postmenopausal glucose and diastolic blood pressure levels and risk of MetS were related to chronological aging. Adiponectin was strongly correlated with all components of the MetS except for blood pressure. Conclusions: Reporting of age at FMP is unreliable in subjects interviewed ≥ 4 years after the event. The STRAW+10 criteria are accurate in staging reproductive aging, as confirmed by the significant association of FSH and estradiol levels with menopausal transition stage. These guidelines may be appropriate for use in resource-limited settings in the absence of biomarkers. The MT in these women is characterized by lower whole body lean mass and BMD in post- compared to premenopausal subjects but there are negligible differences in fat mass. Lower lean mass and BMD were associated with higher FSH and lower E2 serum levels, respectively. Lower fat mass and BMC were associated with ART use. The lipid profile was more atherogenic and blood pressure was higher in the post- than the premenopausal women. These differences were related to the higher FSH (LDL and total cholesterol) and lower E2 (diastolic blood pressure) levels in the postmenopausal women. These data suggest that the hormonal changes characterizing the menopause may play a role in the etiology of cardiometabolic disease and in the body composition changes that are observed in the MT. The above conclusions should be addressed in longitudinal studies. The terminology of STRAW+10 needs to be simplified and the questions contextualized, and contraceptive use should be specifically addressed in questions on bleeding patterns. In addition there are implications for the use of behavioral interventions in lowering cardio-metabolic risk factors and hence morbidity and mortality in these women. Further research is needed to examine health risks associated with snuff use, and the longterm effects of HIV-infection and different ART regimens. Additional studies should address the poor understanding of menopausal health consequences in this population with appropriate education programs
A thesis submitted to the faculty of health sciences, University of the Witwatersrand in fulfilment of the requirements for the degree of doctor of philosophy Johannesburg, South Africa 2015